High‐Conductivity–Dispersibility Graphene Made by Catalytic Exfoliation of Graphite for Lithium‐Ion Battery. (13th November 2020) - Tao, Ran; Li, Fan; Lu, Xing; Liu, Fang; Xu, Jinhui; Kong, Dejia; Zhang, Chen; Tan, Xinyi; Ma, Shengxiang; Shi, Wenyue; Mo, Runwei; Lu, Yunfeng
Abstract: Despite the progress made on the production of graphene using liquid‐phase exfoliation methods, the fabrication of graphene with both high conductivity and dispersibility remains challenging. Through catalytic exfoliation of graphite, an effective synthesis method for graphene with large lateral size (≈10 µm), high conductivity (926 S cm –1 ), and excellent water solubility (≈10 mg mL –1 ) is reported herein. Such graphene can be used broadly for applications such as lithium ion batteries, where both high conductivity and dispersibility are required. As an example, the synthesis of graphene and lithium‐iron‐phosphate composites is demonstrated, which leads to electrodes with dramatically improved cycling stability and rate performance. Adaption of such material leads to electrodes with volumetric energy density as high as 658.7 and 287.6 W h L –1 under 0.5 and 20 C, respectively, which is significantly higher than that of commercial LiFePO4 (394.7 and 13.5 W h L –1 at 0.5 and 20 C, respectively). This work provides a new method of making high‐conductivity–dispersibility graphene for various applications. Abstract : This work reports an effective synthesis of graphene with a large lateral size, high conductivity, and excellent water solubility through catalytic exfoliation of graphite. To examine its use in lithium ion batteries, such a graphene is further assembled with LiFePO4 through spray drying to form a composite cathode, which leads to a dramatically improved cycling stability and rate performance.